Efficacy of antimicrobial peptide LL-37 against biofilm forming Staphylococcus aureus strains obtained from chronic wound infections. (January 2022) - Demirci, Mehmet; Yigin, Akin; Demir, Cemil
Abstract: The antimicrobial peptide LL-37 showed inhibitory effects against Staphylococcus aureus strains, which often responsible for wound infections. Understanding the molecular mechanisms of biofilm-containing wound infections is important. Thus, this study aimed to investigate both the antimicrobial and biofilm efficacy of LL-37 against biofilm-positive methicillin-susceptible S. aureus (MSSA) strains and biofilm-positive methicillin-resistant S. aureus (MRSA) strains obtained from chronic wound infections and its effect on different quorum sensing and virulence genes at suboptimal concentrations. Fifteen biofilm-forming MRSA and 15 biofilm-forming MSSA strains were included in this study. The minimum inhibitory concentration (MIC) values and biofilm formation were tested by microdilution methods. Real-time PCR was performed to determine gene expression levels. MIC values for LL-37 were 89.6 mg/L and 132.3 mg/L for MSSA and MRSA strains, respectively. No statistically significant difference was found between MRSA and MSSA strains in terms of the effect of LL-37 on biofilm formation. A statistically significant difference was found between MRSA and MSSA strains for atlA, RNAIII, and agrA gene expression levels following exposure to a suboptimal concentration of LL-37. Ultimately, the required LL-37 antimicrobial concentration was quite high; however, LL-37 antibiofilm concentration may be acceptable for use in humans against biofilm-forming MRSA and MSSA strains. This is the first study to investigate to effect of a suboptimal LL-37 concentration on gene expression levels of biofilm-forming MSSA and MRSA strains. LL-37 affected quorum sensing and biofilm producing mechanisms, even at suboptimal MIC concentrations. Graphical abstract: Image 1 Highlights: The cationic antimicrobial peptide LL-37 can be used against the biofilm activity of S.aureus in wound infections. MIC values of LL-37 were found 89.6 mg/L and 132.3 mg/L for biofilm forming MSSA and MRSA strains respectively. This is the first study to investigated molecular mechanisms on biofilm forming MSSA and MRSA strains against of LL-37. LL-37 affected quorum sensing and biofilm gene expression of S. aureus in suboptimal MIC concentration.